SERVICE IMPROVEMENT AND SUSTAINABILITY STRATEGY OF WATER SUPPLY AND SANITATION COMMUNITY-BASED (PAMSIMAS) IN INDRAGIRI HULU REGENCY - herlinda, dwi (Jurnal Niara, 2018)
This research is about Strategy of Water supply and sanitations Community Based Sanitation (Pamsimas) In Indragiri Hulu Regency. This research is useful to find a solution. The problem in this research is that the pamsimas program, water service only fulfills <20% of service target facilities.that have been built not functioning optimally From 108 villages only 62 villages with well-built infrastructure and 23 partially functioning villages. Asmoko (2013) Fishbone analysis is a tool that is the only thing and the factors that cause it. This fishbone or fishbonediagram analysis shows the circumstances by looking at the effects and causes that contribute to this category with the categories of Labor, Machine, Methods, Materials, and Media. This study aims to find strategies for improvement and management that have been built. qualitative research with a Fishbond analysis approach. That will be OK to make a decision for. Based on the results of research the main cause in poor achievement of net service target of PAMSIMAS program is the weakness of human resources. The Strategy of Service Improvement and Success of PAMSIMAS Program with training.